Trauma Psikologis pada Penyintas Kekerasan Seksual Intra-Familial - Wahyuni , Hera; Rahmah Ramadhoni, Sri (At-Taujih : Bimbingan dan Konseling Islam, 2026)
Abstrak : This study is motivated by the high incidence of intra-familial sexual violence that causes psychological impacts on victims. Psychological trauma resulting from sexual violence within the family affects emotional conditions, social functioning, academic performance, and interpersonal relationships. This study aims to describe the psychological trauma experienced by victims of intra-familial sexual violence. This study employed a qualitative approach using a case study method. The study involved one participant and two key informants, namely the victim’s mother and a psychologist. Participants were selected using purposive sampling techniques. Data were collected through in-depth interviews, observation, and documentation. The data were analyzed using thematic analysis through transcription, coding, theme categorization, and data interpretation processes. The results showed that the victim experienced psychological trauma in the form of fear, anxiety, sadness, shame, and guilt. The trauma was reflected in various behaviors such as frequent crying, avoiding interaction with others, difficulty sleeping, experiencing nightmares and flashbacks, withdrawing from the social environment, decreased concentration and academic motivation, distrust of others, difficulty establishing interpersonal relationships, and a tendency to isolate herself. Nevertheless, the victim demonstrated adaptive coping by seeking help, obtaining social support from close individuals, and participating in psychological counseling. This study concludes that intra-familial sexual violence causes complex and multidimensional psychological trauma, requiring comprehensive psychological and social support for the victim’s recovery. Keywords: psychological trauma, sexual violence, intra-familial, university student, case study